Association between Blood Pressure and 6 Minutes Walk Distance on Elderly Pilgrims - MT Hapsito (ACI (Acta Cardiologia Indonesiana), 2017)
Introduction: Hypertension as one of the cardiovascular disease risk factors was known to be .....